2022
DOI: 10.47577/tssj.v28i1.5935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IT capability on Performance of Manufacturing Firms in Nairobi City County Kenya

Abstract: Although manufacturing firms support economic development, wealth creation and poverty alleviation, a dismal performance has been reported. In Kenya, the share of gross domestic product (GDP) from manufacturing sector has remained below 10 per cent while its growth rate remained at about 5 percent in the last 10 years. This has been attributed to low innovation and technology diffusion. This study examined the effects of IT capability on firm performance. The study was anchored on Resource Based View, and Dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…According to the results, most of the respondents agreed that their bank played an important role in ensuring lenders can obtain the funding they need to offer borrowers mortgages with attractive interest rates. In line with these findings, Gitau (2014) argued that there is a positive linear relationship between interest rate spread and the financial performance of mortgage lending institutions. Also, tier 1 banks have a large interest spread compared to tier 2 and tier 3 banks.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…According to the results, most of the respondents agreed that their bank played an important role in ensuring lenders can obtain the funding they need to offer borrowers mortgages with attractive interest rates. In line with these findings, Gitau (2014) argued that there is a positive linear relationship between interest rate spread and the financial performance of mortgage lending institutions. Also, tier 1 banks have a large interest spread compared to tier 2 and tier 3 banks.…”
Section: Discussionmentioning
confidence: 63%
“…However, Nyanyuki and Omar (2016) did not treat performance of mortgage lending as an independent variable, but as a dependent variable, hence did not assess how various factors influencing the performance of mortgage lending would influence the supply of mortgage products. On the other hand, there is a positive linear relationship between interest rate spread and financial performance of mortgage lending institutions, according to research results by Gitau (2014). Also, tier 1 banks have large interest spread compared to tier 2 and tier 3 banks.…”
Section: The Capital Buffer Theorymentioning
confidence: 90%
“…If learners change values and have positive interaction with the environment, issues relating the environmental degradation are likely to be addressed. Gitau (2015) explains that that 'explanatory method' is largely a passive process and does not arouse learners' interest. This gives a clear picture that the method would not address environmental degradation because learners' thinking would not be transformed.…”
Section: Discussion On Objective 2: Investigating the Appropriateness...mentioning
confidence: 99%
“…A case study is a narrative account of a series of events or situations that relate to a specific issue that might relate to the lives of the participants (Chakwera, et al 2003). Gitau (2015) recommends Case study method as a strategy of teaching since it involves problem-based learning and promotes the development of analytical skills in learners. This means that a case study in Biology involves students in solving problems that may be similar to those they face in their daily lives.…”
Section: Teaching and Learning Methods Related To Environmental Degra...mentioning
confidence: 99%
“…A study conducted by (Gitau, 2022) concluded that the IT staff and managers of businesses should actively engage with business units to foster efficient information technology utilization through the exchange of business-related knowledge. Managers of businesses should spend money planning, organizing, coordinating, and controlling how they use IT.…”
Section: Statement Of the Problemmentioning
confidence: 99%